Reflexion on Bio-Sourced Mosquito Repellents: Nature, Activity, and Preparation - Grison, Claude; Carrasco, David; Pelissier, Franck; Moderc, Alexandra (Frontiers in Ecology and Evolution, 2020)
Over the last decades, the geographical distribution of certain mosquito species carrying vector-borne diseases has considerably expanded. They represent a major health concern as they transmit pathogens causing alarming epidemics. In the absence of vaccines for most of the mosquito-borne diseases, the use of topical mosquito repellents is one of the main measures to prevent human-mosquito contacts. Synthetic repellents are the most used mosquito repellents. However, several concerns about their safety for consumers have led to a growing demand of natural alternatives. Here we present an overview of the most commonly used natural-based mosquito repellents: repellent activity, biological action, composition, stereochemical structure (when appropriate) and syntheses, paradoxically far from being eco-friendly. We discuss on future prospective that would combine sustainable chemical processes and synergistic effects promising for the development of natural, safe and efficient topical repellents.